2000
DOI: 10.1017/s0963548300004259
|View full text |Cite
|
Sign up to set email alerts
|

Algorithmic Aspects of Partial List Colourings

Abstract: Let G = (V , E) be a graph with n vertices, chromatic number χ(G) and list chromatic number χ (G). Suppose each vertex of V (G) is assigned a list of t colours. Albertson, Grossman and Haas [1] conjectured that at least t χ (G) n vertices can be coloured properly from these lists.Albertson, Grossman and Haas [1] and Chappell [3] proved partial results concerning this conjecture. This paper presents algorithms that colour at least the number of vertices given in the bounds of Albertson, Grossman and Haas, and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The proof of Theorem 3 in uses the probabilistic method. In , Voigt gave an algorithmic proof of this result. The proof of Theorem 7 below uses a combination of ideas from and from .…”
Section: The Proofsmentioning
confidence: 95%
See 1 more Smart Citation
“…The proof of Theorem 3 in uses the probabilistic method. In , Voigt gave an algorithmic proof of this result. The proof of Theorem 7 below uses a combination of ideas from and from .…”
Section: The Proofsmentioning
confidence: 95%
“…In , Voigt gave an algorithmic proof of this result. The proof of Theorem 7 below uses a combination of ideas from and from . Lemma If ch OL (G)=s and t<s, then V(G) can be partitioned as V=XY such that ch OL (G[X])t and χ(G[Y])st. Proof Assume the Lister and the Painter play the (G,s)‐list coloring game on G .…”
Section: The Proofsmentioning
confidence: 95%
“…Albertson, Grossman, and Haas [2] introduced partial list coloring with a "frankly mischievous" intent of inciting further work. Indeed, this has received attention in several papers [2,12,15,16,17,18,29]. Given a list assignment L, we want to properly L-color as many vertices as possible.…”
Section: Partial List Coloringmentioning
confidence: 99%
“…(see [2,29]), α ℓ t (G) > 6 7 (t|V (G)|/χ ℓ (G)) (see [12]), and [15,16]). The Partial List Coloring Conjecture has been proven for bipartite graphs (by the bound from [2,29]), graphs G with ∆(G) ≤ χ ℓ (G) (see [17]), claw-free graphs, chordless graphs, chordal graphs, series parallel graphs, and graphs G satisfying |V (G)| ≤ 2χ(G) + 1 (see [18]). Iradmusa [16] also showed that for every graph G, the inequality in Conjecture 1 holds for at least half the values of t in [χ ℓ (G) − 1].…”
Section: Partial List Coloringmentioning
confidence: 99%